Design och implementation av en webbsida med tillhörande administrationssystem - Afshar, Madeleine; Podgornoj, Linnea (My University, 2008)
This report describes how the process has evolved during the creation of a new web page for the company Scandinavian Travel Agent DMC. The design methods that have been used are described and also how parts of the webpage have been created by using the design method results. Our reflections around design and functionality are explained and how usability has been our main focus during the master thesis. We also describe how it has been to work with an external costumer and how the tasks constantly have changed and been added as the process has continued. The background to this work is that AB Scandinavian Travel Agent DMC need to improve their current web page. This to give the clients better needed information about destinations, but also to stand out in the competitive travel business. The result is a functioning web page and administration system that has a focus on usability and also reflects the personalized services that the company provides.
Keywords: Information Technology; Informationsteknik